The institutionalization of the problems of destructive information and psychological impact on the population of the member countries of the Organization in the CSTO regulatory documents - V. M. Strugovets; I. A. Gereikhanova (Современная наука и инновации, 2024)
The article addresses the issues of the destructive information and psychological impact of the collective west on the population of the post-Soviet space, including the member states of the Collective Security Treaty Organization and their institutionalization in the regulatory and statutory documents of the CSTO. The path of the problem under study was analyzed: from the complete absence of the CSTO in official documents to the recognition of "priority" in matters of ensuring collective security and bringing information threats to the same level with threats from the military, political, economic and terrorist. The content of the basic concepts and terms of the information security sphere related to the aspect of destructive information and psychological impact has been clarified.